2008
DOI: 10.1074/jbc.m709153200
|View full text |Cite
|
Sign up to set email alerts
|

pLG72 Modulates Intracellular D-Serine Levels through Its Interaction with D-Amino Acid Oxidase

Abstract: Human genes coding for pLG72 and D-amino acid oxidase have recently been linked to the onset of schizophrenia. pLG72 was proposed as an activator of the human FAD-containing flavoprotein D-amino acid oxidase (hDAAO). In the brain this oxidizes D-serine, a potent activator of N-methyl-D-aspartate receptor. We have investigated the mechanistic regulation of hDAAO by pLG72. Immunohistochemical analyses revealed that hDAAO and pLG72 are both expressed in astrocytes of the human cortex, where they most likely inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
277
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 139 publications
(291 citation statements)
references
References 34 publications
(45 reference statements)
10
277
1
1
Order By: Relevance
“…We also demonstrated that CPZ binds to the apoprotein form of hDAAO with an affinity similar to that estimated for FAD. 9 Furthermore, and differently to that observed for FAD binding, the presence of benzoate does not modify the K d for CPZ binding to hDAAO apoprotein.…”
Section: Effect Of Ligand Binding On the Conformation Of Hdaaomentioning
confidence: 75%
See 4 more Smart Citations
“…We also demonstrated that CPZ binds to the apoprotein form of hDAAO with an affinity similar to that estimated for FAD. 9 Furthermore, and differently to that observed for FAD binding, the presence of benzoate does not modify the K d for CPZ binding to hDAAO apoprotein.…”
Section: Effect Of Ligand Binding On the Conformation Of Hdaaomentioning
confidence: 75%
“…The aliphatic phenothiazine CPZ is a dopamine D2 receptor antagonist that was introduced in the treatment of schizophrenia in the early 1950s; it also acts as a FAD-competitive inhibitor of hDAAO (K d ¼ 5 lM). 9,17 We here demonstrate that the different ligands affect the conformation and stability of the holoenzyme and apoprotein forms of the human flavoenzyme as well as the cellular concentration of hDAAO differently. We also provide evidence that these ligands do not alter the interaction between hDAAO and pLG72 and that affect the time course of cellular D-serine concentration similarly.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations